BLIND STICK UNTUK PENYANDANG TUNA NETRA BERBASIS ARDUINO - M.Raihan Alpinsyah; Novita Wulandari; Ririn Yuniar; Reny Annisa Witr; Nyimas Anniz Soufani; Seh Arya Dini; Nurhajar Anugraha; Rapiko Duri (Teknik Elektro Polsri, 2026)
The development of microcontroller technology opens up significant opportunities for the development of mobility aids for people with disabilities, particularly the visually impaired. This research designed and developed an Arduino-based Blind Stick that helps users detect obstacles around them. The system utilizes an ultrasonic sensor for distance detection, a buzzer for audio alerts, and a vibration module to provide tactile feedback when an object is within a certain distance. Data received by the sensor is processed by an Arduino microcontroller, enabling a fast and accurate response. Test results indicate that the device is capable of detecting objects within an effective range according to the user's mobility needs and providing easy-to-understand alerts. Therefore, this Arduino-based Blind Stick is expected to improve the safety, independence, and quality of life of visually impaired users in their daily activities